Treating Prey With Glyphosate Does Not Alter the Demographic Parameters and Predation of the Harmonia axyridis (Coleoptera: Coccinellidae) - Saska, Pavel; Skuhrovec, Jirí; Lukáš, Jan; Vlach, Miroslav; Chi, Hsin; Tuan, Shu-Jen; Honek, Alois (Journal of economic entomology, 2017)
Glyphosate is an herbicide that is used worldwide with potential environmental risks to nontarget organisms. We applied an age-stage, two-sex life table approach to assess the sublethal effects of short-term oral exposure to a glyphosate-based herbicide on the life table parameters and biocontrol potential of Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae). Aphids (Metopolophium dirhodum (Walker) (Sternorrhyncha: Aphididae)) treated with herbicide (an isopropylamine-salt of glyphosate) at low recommended, maximum recommended, and double the maximum recommended concentration for agricultural situations, and untreated controls were offered to the fourth instar of H. axyridis for 24 h. Development, consumption, and fecundity were measured daily until death. We detected minor differences in the hatching rate and mean generation time, whereas the longevity, fecundity, net reproductive rate, intrinsic rate of increase, finite rate of increase, and consumption were unaffected across treatments. We conclude that biocontrol potential of H. axyridis was not affected by acute oral intoxication by a glyphosate-based herbicide during the larval stage for 24 h under the study design.
Keywords: glycin; Animals; Life History Traits; mšice; Female; Food Chain; Coleoptera; Insecticides; aphidophagy; ženské pohlaví; nymfa; Pupa; Aphids; brouci; Glyphosate; Predatory Behavior; glyfosát; Harlequin lady beetle; Nymph; life table, biocontrol potential; Male; biologická kontrola škůdců; zvláštnosti životní historie; insekticidy; Pest Control, Biological; Glycine; predátorské chování; Larva; zvířata; mužské pohlaví; potravní řetězec; kukla; Roundup; larva